Reappraisal of the suitability of corneas from bacteremic donors for use in corneal transplants. Issue 8 (15th October 2018) - Chu, Hsiao-Sang; Lai, Chun-Ting; Hou, Yu-Chih; Liu, Hsin-Yu; Wang, I-Jong; Chen, Wei-Li; Shih, Chung-Liang; Hu, Fung-Rong
Abstract : Background: This study examined whether corneas from bacteremic donors could be used for corneal transplant. Methods: Corneas donated to the National Eye Bank of Taiwan between 1 January 2014 and 30 June 2017 were included in this study. All the corneas had corneoscleral rim cultures during the retrieval process and were hypothermic preserved in the Optisol-GS storage medium. A microbial work-up flow chart was used for the sterility check of all grafts. Bacteremic donors were defined as those whose last blood culture before corneal donation was positive. The microbial contamination rates, the endothelial cell densities, the tissue utility rates and early complications after transplants were compared between the corneas from bacteremic versus non-bacteremic donors. Results: 697 corneas from 356 donors were analysed, 70 of which were from bacteremic donors. The microbial contamination rates of the corneas from bacteremic and non-bacteremic donors (7.1% vs 9.1%)(p=0.30) were close. None of the contaminated corneas grew the same bacterial strains as those from their blood cultures. The corneas from bacteremic donors and non-bacteremic donors have similar endothelial cell densities (2931±297 cells/mm 2 vs 2903 ± 470 cells/mm 2 ) (p=0.63). Corneas from bacteremic and non-bacteremic donors shared a similar utility rate (98.6% vs 99.4%)(p=0.41). None of the corneas caused infectious complications after transplants. Conclusion: Our study showed that corneas from bacteremic and non-bacteremic donors have equally low contamination rates and are of the same quality in terms of endothelial cell density and safety.